2013
DOI: 10.1182/blood-2013-05-505180
|View full text |Cite
|
Sign up to set email alerts
|

The histone methyltransferase Ezh2 is a crucial epigenetic regulator of allogeneic T-cell responses mediating graft-versus-host disease

Abstract: Key Points Ezh2 is specifically required to induce effector cells producing IFN-γ and expansion of T cells late upon alloantigen activation. Genetic inactivation of Ezh2 function reduces GVHD but preserves antitumor effects in mice after allogeneic BMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 51 publications
12
75
0
Order By: Relevance
“…We demonstrated that Ezh2 maintains the survival of effector Th0 cells by suppression of extrinsic and intrinsic death receptor pathways. This is consistent with a recent study 39 …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We demonstrated that Ezh2 maintains the survival of effector Th0 cells by suppression of extrinsic and intrinsic death receptor pathways. This is consistent with a recent study 39 …”
Section: Discussionsupporting
confidence: 83%
“…For example, depletion of Bim was insufficient to rescue Ezh2-mediated cell death. 39 Cell death is unlikely to be a consequence of excessive IFN-g production because (1) significant cell death was observed in Th2 and Th17 cells under differentiation conditions that did not result in IFN-g production; and (2) Q-VDOph rescued Ezh2 fl/fl .CD4Cre Th0 cell death without altering IFN-g production. Future experiments are required to identify potential transcription factors that enhance the expression of death receptors and/or their ligands.…”
Section: In Which Donormentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Loss of EZH2 in T cells specifically impairs their differentiation into interferon (IFN)-g-producing effector cells. 35 In the context of clinical tumor immunity, it has been reported that EZH2 enforces the cytotoxicity of CTLs against ovarian tumors by silencing the Notch repressors NUMB and FBXW7. 36 We speculated that this could be a general mechanism employed by CTLs in our NSCLC context.…”
Section: Discussionmentioning
confidence: 99%
“…This was first identified in allogeneic CTL responses mediating graft-versus-host disease. 22 Recently, in the TME, it was identified that EZH2 supports CTL-mediated antitumor immunity by silencing repressors of Notch signaling. In addition, the clinical relevance of EZH2 expression in ovarian cancer highlights that it is part of a major pathway targeted by the TME for immunosuppression.…”
Section: Introductionmentioning
confidence: 99%